Pengetahuan Tradisional Belacan Habang (Terasi Toboali) Sebagai Warisan Budaya (Bumbu Tradisional) Khas Toboali Kabupaten Bangka Selatan - Dhaswara , Dwikki Ogi; Jamil, Muhammad Safwan (JURNAL GASTRONOMI INDONESIA, 2025)
South Bangka is a region rich in natural resources. This wealth has long been influenced by external cultures. This richness has made South Bangka rich in cultural diversity, a blend of diverse ethnicities. Belacan is a traditional knowledge, including traditional food from South Bangka, a traditional spice used as a complement to cooking spices and food flavoring. This traditional spice, a fermented seafood product with a unique aroma and flavor, is a cottage industry product commonly found in coastal communities in South Bangka. Belacan habang, as a cultural heritage of South Bangka Regency, has significant cultural and economic value. This processed shrimp product has become a communal intellectual property and has been passed down for over a century. Although its existence has long been recognized, the pattern of inheritance of traditional knowledge regarding the production of belacan habang began to be documented in 1931. The results of the study indicate that belacan habang is not merely a culinary product, but a symbol of tradition and local knowledge as a traditional spice that has survived the tide of modernization. The protection and preservation of belacan habang as an intangible cultural heritage is crucial in maintaining the sustainability of this tradition for future generations.